Desmoteplase 3 to 9 Hours After Major Artery Occlusion Stroke: The DIAS-4 Trial (Efficacy and Safety Study of Desmoteplase to Treat Acute Ischemic Stroke). Issue 12 (December 2016) - von Kummer, Rüdiger; Mori, Etsuro; Truelsen, Thomas; Jensen, Jens-Kristian S.; Grønning, Bjørn A.; Fiebach, Jochen B.; Lovblad, Karl-Olof; Pedraza, Salvador; Romero, Javier M.; Chabriat, Hugues; Chang, Ku-Chou; Dávalos, Antoni; et al.
Abstract : Background and Purpose—: The DIAS-3 trial (Efficacy and Safety Study of Desmoteplase to Treat Acute Ischemic Stroke [phase 3]) did not demonstrate a significant clinical benefit of desmoteplase administered 3 to 9 hours after stroke in patients with major artery occlusion. We present the results of the prematurely terminated DIAS-4 trial together with a post hoc pooled analysis of the concomitant DIAS-3, DIAS-4, and DIAS-J (Japan) trials to better understand the potential risks and benefits of intravenous desmoteplase for the treatment of ischemic stroke in an extended time window. Methods—: Ischemic stroke patients with occlusion/high-grade stenosis in major cerebral arteries were randomly assigned to intravenous treatment with desmoteplase (90 μg/kg) or placebo. The primary outcome was modified Rankin Scale (mRS) score of 0 to 2 at day 90. Safety assessments included mortality, symptomatic intracranial hemorrhage, and other serious adverse events. Results—: In DIAS-4, 52 of 124 (41.9%) desmoteplase-treated and 46 of 128 (35.9%) placebo-treated patients achieved an mRS score of 0 to 2 (odds ratio, 1.45; 95% confidence interval, 0.79; 2.64; P =0.23) with equal mortality, frequency of symptomatic intracranial hemorrhage, and other serious adverse events in both the treatment arms. In the pooled analysis, mRS score of 0 to 2 was achieved by 184 of 376 (48.9%) desmoteplase-treated versus 171 of 381 (44.9%) placebo-treated patients (odds ratio, 1.33; 95% confidence interval, 0.95; 1.85; P =0.096). Treatment with desmoteplase was safe and increased the recanalization rate (107/217 [49.3%] versus 85/222 [38.3%]; odds ratio, 1.59; 95% confidence interval, 1.08–2.35; P =0.019). Recanalization was associated with favorable outcomes (mRS 0–2) at day 90 in both the treatment arms. Conclusions—: Late treatment with intravenous 90 µg/kg desmoteplase is safe, increases arterial recanalization, but does not significantly improve functional outcome at 3 months. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00856661. Abstract : Supplemental Digital Content is available in the text.